Jaringan Kebijakan Dalam Implementasi Mobile SIMPEG Untuk Meningkatkan Disiplin PNS: Studi Pada IPDN Kampus NTB - I Gusti Ayu Putu Aryanti; Rulinawaty Rulinawaty; Milwan Milwan (Jayapangus Press, 2026)
The development of information technology has encouraged innovation in managing civil servant discipline, including through the implementation of the Mobile Personnel Management Information System (Mobile SIMPEG) within the Ministry of Home Affairs. This application is designed to enhance objectivity and accuracy in monitoring employee attendance. However, in practice, several challenges persist, such as the exploitation of system loopholes by some employees, limited direct supervision, and suboptimal coordination among actors within the policy network. This study aims to analyze the effectiveness of the policy network in the implementation of Mobile SIMPEG at the Secretariat of IPDN Nusa Tenggara Barat Campus. This research employs a qualitative method with a case study approach. Data were collected through in-depth interviews, observation, and documentation involving 15 informants consisting of leaders, operators, and administrative staff. The analysis focuses on key dimensions of the policy network, including actors, functions, structure, institutionalization, rules of conduct, power relations, and actor strategies. The findings indicate that the policy network has been established and is functioning; however, its effectiveness remains moderately effective, yet not optimal. The network structure tends to be hierarchical, with a high dependence on central actors, while coordination among actors is still limited and often informal. In addition, the absence of detailed standard operating procedures (SOPs) at the local level results in variations in policy implementation. From an implementation perspective, communication is not consistently structured, resources face limitations in digital competence and infrastructure, and implementers’ attitudes vary across units. Therefore, strengthening formal coordination, developing internal SOPs, and enhancing human resource capacity are essential to support a more consistent, integrated, and sustainable implementation of Mobile SIMPEG in improving civil servant discipline.